Dual-Energy Computed Tomography Lung in patients of Pulmonary Tuberculosis - Khan,Ahmad Umar; Khanduri,Sachin; Tarin,Zikra; Abbas,Syed Zain; Husain,Mushahid; Singh,Anchal; Yadav,Poonam; Jain,Shreshtha (Journal of Clinical Imaging Science)
Objectives: The objective of this study was to characterize findings of high-resolution computed tomography (HRCT) and dual-energy CT (DECT) (80 keV, 140 keV, and mixed) in pulmonary tuberculosis (TB) patients and to compare and correlate HRCT and DECT findings. Material and Methods: This cross-sectional study was conducted on 67 patients of 18–65 years of age who were suspected cases of pulmonary TB with signs and symptoms of cough, fever, hemoptysis, sputum, night sweats, and weight loss with positive sputum AFB examinations/bronchoalveolar lavage. All the patients subjected to HRCT scan and followed with DECT scan. Comparison of various imaging techniques (DECT 80 keV, DECT 140 keV, and DECT mixed) with HRCT was done for detecting lung findings and data so obtained were subjected to statistical analysis. Results: On comparing the various imaging techniques with HRCT for detecting consolidation, tree in bud pattern, cavitary lesions, ground-glass opacity, bronchiectasis, atelectasis, nodules, granuloma, peribronchial thickening, and fibrosis, the maximum agreement of HRCT was found with DECT 80 keV and minimum agreement was found with DECT 140 keV. Conclusion: The study concluded that DECT 80 keV monochromatic reconstructions among 80 keV, mixed, and 140 keV monochromatic reconstructions in lung parenchyma window settings are a faster and better analytical tool for the assessment of findings of pulmonary TB when compared with HRCT.